Mentoring Pemimpin Rohani Sebagai Tugas Dosen Sekolah Tinggi Teologi Injili Arastamar Ngabang - Marthen Mau; Sulianus Susanto; Aprinia Windasari; Risky Permana Hutabarat; Septinus Hia (Didache: Journal of Christian Education, 2023)
Students of the Arastamar Evangelical Theology College (SETIA) Ngabang as spiritual leaders must have good skills, leadership, and personality which are very much needed today for church services and in Christian educational institutions because they need mentoring by SETIA Ngabang lecturers. Some of SETIA Ngabang's theology students have not shown the maximum skills and personality to handle spiritual services even though graduate users need their energy. To produce accurate research, qualitative research methods are used with observation and interview approaches as options; as well as the sources of literature as a support in this research. Mentoring spiritual leaders at SETIA Ngabang can be done by lecturers who have special knowledge and experience in certain fields according to their expertise, because spiritual leaders are needed to have the fear of God, respect, humility, spirituality, integrity, competence, qualifications, credibility, and loyalty in spiritual ministry, both in the church and in Christian educational institutions. The theoretical implication of the research is that SETIA Ngabang lecturers and students who do not yet have skills in certain fields, competitiveness in leadership, and personality in carrying out responsibilities at SETIA Ngabang to the maximum need to be mentored to be able to show capabilities in their service. The implementation of mentoring can improve performance, commitment, motivation, awareness, and better self-reflection so that leadership ability is getting better as well.